Effect of azoxystrobin on tobacco leaf microbial composition and diversity - Sun, Meili; Wang, Hancheng; Shi, Caihua; Li, Jianjun; Cai, Liuti; Xiang, Ligang; Liu, Tingting; Goodwin, Paul H.; Chen, Xingjiang; Wang, Ling (Frontiers in Plant Science, 2023)
Azoxystrobin, a quinone outside inhibitor fungicide, reduced tobacco target spot caused by Rhizoctonia solani by 62%, but also affected the composition and diversity of other microbes on the surface and interior of treated tobacco leaves. High-throughput sequencing showed that the dominant bacteria prior to azoxystrobin treatment were Methylobacterium on healthy leaves and Pseudomonas on diseased leaves, and the dominant fungi were Thanatephorous (teleomorph of Rhizoctonia) and Symmetrospora on healthy leaves and Thanatephorous on diseased leaves. Both bacterial and fungal diversity significantly increased 1 to 18 days post treatment (dpt) with azoxystrobin for healthy and diseased leaves. For bacteria on healthy leaves, the relative abundance of Pseudomonas, Sphingomonas, Unidentified-Rhizobiaceae and Massilia declined, while Methylobacterium and Aureimonas increased. On diseased leaves, the relative abundance of Sphingomonas and Unidentified-Rhizobiaceae declined, while Methylobacterium, Pseudomonas and Pantoea increased. For fungi on healthy leaves, the relative abundance of Thanatephorous declined, while Symmetrospora, Sampaiozyma, Plectosphaerella, Cladosporium and Cercospora increased. On diseased leaves, the relative abundance of Thanatephorous declined, while Symmetrospora, Sampaiozyma, Plectosphaerella, Cladosporium, Phoma, Pantospora and Fusarium, increased. Compared to healthy leaves, azoxystrobin treatment of diseased leaves resulted in greater reductions in Thanatephorous, Sphingomonas and Unidentified-Rhizobiaceae, a greater increase in Methylobacterium, and similar changes in Phoma, Fusarium, Plectosphaerella and Cladosporium. Azoxystrobin had a semi-selective effect altering the microbial diversity of the tobacco leaf microbiome, which could be due to factors, such as differences among bacterial and fungal species in sensitivity to quinone outside inhibitors, ability to use nutrients and niches as certain microbes are affected, and metabolic responses to azoxystrobin.